The Role of Ethical Leadership On Reduce Organizational Cynicism, An Analytical Study of a Sample of Faculty Members in Salaheddine Erbil University Faculties - Mudhafar Hamad Ali; Ahlam Ibrahim Waly (QALAAI ZANIST JOURNAL, 2020)
The research aims to study the role of ethical leadership in reducing the organizational cynicism. The problem of research was identified by asking several questions focused on the nature of the relationship and impact between the two variables. The design of a hypothetical research plan, which resulted in several main and sub-hypotheses that were subjected to the set of statistical tests. The research followed the descriptive analytical method. The questionnaire was designed for this purpose and distributed to a sample of the faculties of Salahaldin Erbil University numbering (327). The data collected was valid for analysis. The program (SPSS) was used to study the supposed relationships in the research model. The researcher reached a set of conclusions and proposals, the most important of which is the existence of an inverse relationship and an influence between ethical leadership and organizational cynicism so that the practice of academic leadership for the characteristics of leadership server in colleges reduces the organizational conflict. The researcher recommended the academic leadership in the faculties of Salaheddine Erbil University should work to reduce the belief that academic leaders lack confidence and integrity through preference of public interests over their personal interests and that enhances their credibility and integrity.